Estimates for the best asymmetric approximations of asymmetric classes of functions - Motornyi, V. P.; Pas'ko, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2011)
Asymptotically sharp estimates are obtained for the best (α, β) -approximations of the classes W^r_1; γ, δ with natural r by algebraic polynomials in the mean.